Pemanfaatan Whatsapp Grup sebagai Media Komunikasi di Daerah Pedesaan - Ririn Puspita Tutiasri; Wahyu Santoso; Aulia Rahmawati (Jurnal Ilmu Komunikasi, 2021)
Technological developments are able to change the habits or culture of an area, including the way people communicate. One of the technologies that change the way of socializing is through the Whatsapp application. The focus of this research is how to use Whatsapp groups as a communication medium by the community in Pandowan Village, Galur District, Kulon Progo Yogyakarta. The purpose of this study was to describe the use of Whatsapp groups as a communication medium by the community in Pandowan Village, Galur District, Kulon Progo Yogyakarta. This research method uses descriptive qualitative research. The results of this study indicate that the use of Whatsapp groups as a means of exchanging information on village government with the community and fellow villagers. Utilization through whatsapp groups is used as a means of delivering village government policies, conversations, and discussions between residents about village government policies.